Dynamic performance of self-controlling hydro-pick cutting rock. (March 2016) - Liu, Songyong; Liu, Xiaohui; Cai, Weimin; Ji, Huifu
Abstract: A new self-controlling hydro-pick, which can control water flow automatically, was designed based on hydrodynamic theory. Firstly, the balance of forces acting on the pick was shown to present the operating principle of it, specifically, the force exerted by the water pressure acting over an annual area of the pick. A rock-breaking test bed was developed to study the frictional resistance, dynamic response, flow and rock-breaking characteristics of the self-controlling hydro-pick. The results indicate that, the external and internal diameter of the annual area on the pick should be 40.6 mm and 40 mm, respectively to ensure normal shutdown of the self-controlling hydro-pick at a jet pressure 40 MPa. The opening times (time taken to open the valve) increased with jet pressure and decreased with the cutting depth. For a jet pressure and cutting depth of 40 MPa and 12 mm, respectively, the opening time was 0.035 s. The water flow of the self-controlling hydro-pick was less than that of the common hydro-pick when the diameter of the damping hole was 0.5 mm. The percentage water flow reduction increased with the jet pressure and cutting depth. When the jet pressure and cutting depth are 40 MPa and 12 mm, respectively, the percentage cutting force reduction was 22.6%, the depth of the cutting slot increased by 24.2%, and the volume of rock breakage increased by 29.3%. Graphical abstract: Highlights: A self-controlling hydro-pick was designed to control water flow automatically. Some experiments were developed to study the performance of the new pick. Friction, dynamic response, flow and rock breaking characteristics were studied.